2007
DOI: 10.1007/s00216-007-1604-5
|View full text |Cite
|
Sign up to set email alerts
|

Immobilised tyrosinase-based biosensor for the detection of tea polyphenols

Abstract: An amperometric principle-based biosensor containing immobilized enzyme tyrosinase has been used for detection of polyphenols in tea. The immobilized tyrosinase-based biosensor could detect tea polyphenols in the concentration range 10-80 mmol L(-1). Immobilization of the enzyme by the crosslinking method gave good stable response to tea polyphenols. The biosensor response reached the steady state within 5 min. The voltage response was found to have a direct linear relationship with the concentration of polyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Amperometric laccase-based biosensors for the determination of polyphenols in wines (Gomes and Rebelo 2003;Fernandes and Rebelo 2009) and plant extracts are described (Diaconu et al 2010). Biosensor containing enzyme tyrosinase immobilized by the crosslinking method has been used for detection of polyphenols in tea (Abhijith et al 2007). Biosensor based on the biimmobilization of laccase and tyrosinase phenoloxidase enzymes and the Sonogel-Carbon as electrochemical transducer has been developed for estimation of the total polyphenol index in beer samples (ElKaoutit et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Amperometric laccase-based biosensors for the determination of polyphenols in wines (Gomes and Rebelo 2003;Fernandes and Rebelo 2009) and plant extracts are described (Diaconu et al 2010). Biosensor containing enzyme tyrosinase immobilized by the crosslinking method has been used for detection of polyphenols in tea (Abhijith et al 2007). Biosensor based on the biimmobilization of laccase and tyrosinase phenoloxidase enzymes and the Sonogel-Carbon as electrochemical transducer has been developed for estimation of the total polyphenol index in beer samples (ElKaoutit et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports, the electrochemical detection of TPs was limited to the single component of tea polyphenols separated by HPLC, and the working electrode was without modification. Recently, Abhijith and co-workers [28] reported the detection of TPs with linear range of 10 -80 mM by using tyrosinase-based biosensor. More recently, Comptons group [29] reported the electrochemical sensing of epigallocatechin gallate and epigallocatechin based on the redox reaction of aminophenol/quinoneimine.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [2002] reported the novel use of tyrosinase for the in vitro conjugation of the protein gelatin to the polysaccharide chitosan. Finally, biosensors based on tyrosinases were designed for measuring phenols, polyphenols and pesticides [Abhijith et al, 2007; Tanimoto de Albuquerque and Ferreira, 2007].…”
mentioning
confidence: 99%